The Effect of Internal Communication Toward Employee Work Productivity of PT Telkom Akses Regional Jatim Bali Nusra - Nafi'ah, Zidni Ilma; Setyoningtias, Khasdyah Dwi Dewi (Universitas Negeri Malang, 2024)
The work productivity of PT Telkom Akses Regional Jatim Bali Nusra employees is not optimal due to various problems caused by a lack of cooperation and coordination. Good communication can improve cooperation or coordination to achieve work productivity. This research aims to determine the extent to which internal communication influences the work productivity of PT Telkom Akses Regional Jatim Bali Nusra employees. The research uses quantitative methods and simple regression analysis to test the hypothesis. The research findings show a significance of .000 with an F-value of 36.357 and an R-squared of .236, proving that internal communication significantly impacts employee work productivity. The extent of the influence of internal communication is 23.6%, and other variables outside this research influence the remaining portion. The practical recommendation of the research is to maximize activities or programs that support the implementation of effective and two-way internal communication, re-socialization and application of the company’s internal communication SOP, optimization of communication media within the company, as well as activities that support the maximization of employee work productivity such as employee training related to meeting the quality and quantity of work output, and employee work discipline.